Generic skill requirements: between employer’s aspiration and the need of professional employees - Rosima Alias,; Mohd Izham Mohd Hamzah,; Nora Yahya, (Penerbit Universiti Kebangsaan Malaysia, 2013)
The purpose of this study is to explore the different generic skills (GS) required by employers and the generic skills possessed by professional employees in Malaysia. This study also aims to determine whether there are differences in the GS requirements among employers based upon the size of the organization, type of ownership, and type of organization. A quantitative approach, utilizing questionnaires and interviews, was employed as the main method of collecting data. The sample consists of 141 service-based employers and 167 professional employees. The reliability and validity of the questionnaire items were tested using the Cronbach Alpha and the SEM CFA approaches. The results demonstrate that: (1) 80 percent of the employers lauded on leadership, management, critical thinking, problem solving, social skills and teamwork skills; (2) only 28 percent of the employers require entrepreneurial skills when recruiting new staff; and (3) there is no significant difference in the generic skills required in relation to the size, type, and ownership of the employer. On the other hand, the generic skills rated highly by the employees in the survey are teamwork skills. Entrepreneurship skills received a low rating from both employers and employees during the survey. The implications of this study include a call for further research to determine effective teaching and learning strategies in developing the designated GS, especially for skills that are highly sought after by employers. The originality of this study stems from the lack of literature that directly examines the need for GS among professional employees in the public and private sectors.